Pharmacokinetics and safety after once and twice a day doses of meclizine hydrochloride administered to children with achondroplasia - Kitoh, Hiroshi; Matsushita, Masaki; Mishima, Kenichi; Nagata, Tadashi; Kamiya, Yasunari; Ueda, Kohei; Kuwatsuka, Yachiyo; Morikawa, Hiroshi; Nakai, Yasuhiro; Ishiguro, Naoki (PLOS ONE, 2020)
Achondroplasia (ACH) is the most common short-limbed skeletal dysplasia caused by activating mutations in the fibroblast growth factor receptor 3 (FGFR3) gene. We identified that meclizine hydrochloride inhibited FGFR3 signaling in various chondrocytic cells and promoted longitudinal bone growth in mouse model of ACH. Meclizine has safely been used for more than 50 years, but it lacks the safety data for repeated administration and pharmacokinetics (PK) when administered to children. We performed a phase Ia study to evaluate the PK and safety of meclizine administered orally to ACH children. Twelve ACH children aged from 5 to younger than 11 years were recruited, and the first 6 subjects received once a day of meclizine in the fasted condition, subsequent 6 subjects received twice a day of meclizine in the fed condition. Meclizine was well tolerated in ACH children with no serious adverse events. The mean Cmax, Tmax, AUC0-24h, t1/2 during 24 hours in the fasted condition were 130 ng/mL, 1.7 hours, 761 ng·h/mL, and 8.5 hours respectively. The simulation of repeated administration of meclizine for 14 days demonstrated that plasma concentration apparently reached steady state around 10 days after the first dose both at once a day and twice a day administration. The AUC0-10h of the fasting and fed condition were 504 ng·h/mL and 813 ng·h/mL, respectively, indicating exposure of meclizine increased with the diet. Although higher drug exposure was confirmed in ACH children compared to adults, a single administration of meclizine seemed to be well tolerated.